Hábitos não saudáveis de adolescentes do município de Itaqui/RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This study aimed to describe the unhealthy habits of adolescents in Itaqui/RS, Brazil. 744 individuals from 13 to 19 years, of both sexes, registered in high school of three state schools participated in the research. Information about the life habits were obtained through a self applied questionnaire, and the nutritional status was obtained by body mass index classified for age. The majority of students were female, with a mean age of 15.7 years, auto referred white, belonging to class B, and whose mothers had up to 8 years of study. The prevalence of overweight was approximately 27% in this population. With regard to eating habits, meals with higher omission percentages were supper (59.1%), collation (51.8) and breakfast (45.9%); 19.9% of adolescents hold the food in the maternal ausence, 35.3% feed in front of the TV and 22.5% ingest alcohol in the last month. In addition, 4.0% of the adolescents reported smoking and 37.4% being sedentary. Poor eating habits, such as missed meals, need to be modified because it is related to low intake of nutrients and school performance. The school is the enabling environment for joint actions in order to minimize the complications of adolescent health.
Keywords: Comportamento do adolescente; Hábitos alimentares; Sedentarismo; Tabagismo; Adolescent behavior; Food habits; Sedentary lifestyle; Smoking; CNPQ::CIENCIAS DA SAUDE